Feline sarcomatoid renal cell carcinoma with peritoneal carcinomatosis and effusion. (January 2022) - Wu, BinXi; Kastl, Brandy; Cino-Ozuna, Ada G.; Springer, Nora L.; Thakkar, Ravindra; Biller, David; Whitehouse, William; Easterwood, Loren; Nguyen, Thu Annelise
A 9-y-old, castrated male, domestic medium-hair cat diagnosed previously with chronic kidney disease developed anorexia and vomiting. Ultrasonography revealed abdominal effusion and a left renal perihilar mass. Cytologic evaluation of the peritoneal fluid and mass identified atypical epithelioid cells suspected to be of renal epithelial or possible mesothelial origin. Immunohistochemical (IHC) evaluation of a formalin-fixed, paraffin-embedded peritoneal fluid cell block indicated both pancytokeratin and vimentin expression in the atypical epithelioid cell population. With scanning electron microscopic evaluation, similar epithelioid cells lacked the cell-surface microvilli expected of mesothelium, supporting an antemortem diagnosis of probable carcinoma. On postmortem examination, the left kidney was effaced by an infiltrative neoplasm with myriad similar nodules throughout the peritoneum. The neoplasm was composed primarily of polygonal-to-spindle-shaped cells with strong vimentin and weak pancytokeratin cytoplasmic immunolabeling. Further IHC characterization with PAX8, CK18, KIT, napsin A, SMA, desmin, CD18, and claudin 5 was performed. Histologic and IHC findings supported a diagnosis of sarcomatoid renal cell carcinoma with peritoneal carcinomatosis. An in vitro cell culture line of neoplastic cells harvested from the primary tumor was successfully established for future research endeavors.